Consequences of coronavirus infection: Hemorheological disorders and possibilities for correction - Margarita V. Kruchinina; Andrei A. Gromov; Irina I. Logvinenko; Elina V. Kruchinina (Consilium Medicum)
Aim. To study intravascular changes in hemostasis and changes in electrical, viscoelastic parameters of erythrocytes in COVID-19 convalescents and to evaluate the effectiveness of the pharmacological composition of nicotinamide, cocarboxylase, trifosadenine, cyanocobalamin for intramuscular administration (Cocarnit® drug) and cytidine diphosphocholine (citicoline, Ronocit® drug) to eliminate hemorheological disorders.